2012
DOI: 10.1155/2012/540398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Diagnosis of Acromegaly

Abstract: Acromegaly and gigantism are due to excess GH production, usually as a result of a pituitary adenoma. The incidence of acromegaly is 5 cases per million per year and the prevalence is 60 cases per million. Clinical manifestations in each patient depend on the levels of GH and IGF-I, age, tumor size, and the delay in diagnosis. Manifestations of acromegaly are varied and include acral and soft tissue overgrowth, joint pain, diabetes mellitus, hypertension, and heart and respiratory failure. Acromegaly is a disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 72 publications
2
83
0
20
Order By: Relevance
“…4 Clinical manifestations in each patient are different depending on the delay in diagnosis. 2 Acromegaly is a slowly progressive disease characterized by a 30% increase in mortality rate for cardiovascular disease and respiratory complications of malignancies. Patients with acromegaly generally exhibit coarsened facial features, acral enlargement, soft-tissue hyperplasia, carpal tunnel syndrome, visual abnormalities, headache and sleep apnoea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Clinical manifestations in each patient are different depending on the delay in diagnosis. 2 Acromegaly is a slowly progressive disease characterized by a 30% increase in mortality rate for cardiovascular disease and respiratory complications of malignancies. Patients with acromegaly generally exhibit coarsened facial features, acral enlargement, soft-tissue hyperplasia, carpal tunnel syndrome, visual abnormalities, headache and sleep apnoea.…”
Section: Discussionmentioning
confidence: 99%
“…1 When there is a clinical suspicion of the disease, biochemical confirmation is required to establish the diagnosis. 2 The increase in morbidity and mortality associated with acromegaly is the result of excessive secretion of GH and IGF-1. 1 The earliest manifestations of acromegaly are most commonly hands, feet and/ or facial changes.…”
mentioning
confidence: 99%
“…15 In patients with acromegaly, bromocriptine treatment results in reduction of serum growth hormone levels, 16 which consequently blocks the unfavorable effect of growth hormone on the heart. Several studies have found that early heart attack could be effectively controlled after successful treatment of pituitary tumors, 17,18 thus indicating that early-stage cardiovascular complications are reversible. For example, recent evidence has shown that normalization of growth hormone and IGF-1 can work even in the presence of severe fibrosis in the myocardium.…”
Section: Case Reportmentioning
confidence: 99%
“…Hypersecretion of GH and IGF1 effect the whole body and lead to multisystemic complications, including those involving the gastrointestinal system [2,3]. In terms of organic gastrointestinal disorders, adenomatous polyps and colon carcinoma are the most significant complications associated with acromegaly [4]. Acromegaly has also been related with functional disorders of the gastrointestinal system in several reports.…”
Section: Introductionmentioning
confidence: 99%